Hajj Fund Investment Management: Transparency and Accountability for Indonesian Muslim Society - Herlinda Erni (Athallah Publishing Globalindo, 2025)
Law No. 34 of 2014 on Hajj Financial Management (PKH) provides a clear legal basis for the Hajj Financial Management Agency (BPKH) to regulate the system and management of Hajj funds in Indonesia. This study aims to analyze the financial management mechanisms applied by BPKH, as well as the use of Hajj funds for investment. The research method employed is qualitative, with data and information collected from various sources such as books, research journals, and other references relevant to the topic. The results of the study show that the mechanism for managing Hajj funds begins with the deposit of funds from pilgrims into accounts in the name of BPKH through the Hajj treasury at the Deposit Bank for Hajj Funds (BPS). Subsequently, the allocation of funds for the organization of the Hajj is determined by the government after approval by the DPR (People’s Representative Council), by transferring funds from the Hajj treasury to the Hajj Implementation Unit (PIH) periodically. The assets managed by BPKH include money and goods that can be valued in monetary terms. The use of Hajj funds for investment can take various forms, such as banking products, securities, gold, direct investments, and others. The entire process of managing and investing Hajj funds is carried out based on Sharia principles, with a careful approach to risk management to ensure benefits for the pilgrims and the Muslim community as a whole.